Introduction: Energy Economics and Financial Markets - Simpson, John; Westerman, W.; Dorsman, A. (Springer-Verlag Berlin Heidelberg, 2013)
Energy issues feature frequently in the economic and financial press. It is argued that the importance of energy production, consumption and trade and raises fundamental economic issues that impact the global economy and financial markets. Specific examples of daily energy issues stem from various countries and can often be related to economics and finance. It is shown that energy economics and financial market research issues can be grouped under the themes of supply and demand, environmental impact and renewables, energy derivatives trading, as well as finance and energy.